Improving Student Learning Outcomes Using the Problem Based Learning (PBL) Learning Model on Animal and Plant Material in Class IV SDN 067240 Medan Tembung - Samosir, Friska Natalia; Wahyuni, Sri; Harahap, Lenny Sari (Lembaga Riset Mutiara Akbar, 2025)
This research aims to describe: (1) the use of the Problem Based Learning learning model in class IV at SDN 067240 Medan Tembung and (2) how to improve science learning outcomes for class IV at SDN 067240 Medan Tembung by using the Problem Based Learning learning model. This form of research uses a quantitative-qualitative methodology and is known as classroom action research. Information is collected by tests, observations, interviews, and documentation. Findings showed that 33% of students had completed the pre-cycle learning outcomes, which met their requirements and were still unsatisfactory. The results of the first cycle of learning obtained a student completeness level of 67% which can be said to be quite good. And the second cycle learning results reached a score of 87% with very good qualifications. As a result, learning outcomes improved significantly. According to research, it is proven that the Problem Based Learning learning model can increase student involvement in science subjects, which leads to improved learning outcomes.